Breastfeeding Education Program Based on Human Caring Theory: Randomized Control Trial - Gamze Durmazoğlu; Hülya Okumuş; Merlinda Aluş-Tokat (AVES, 2024)
AIM: The aim of the study was determined to examine the effect of breastfeeding education, counseling, and support based on Human Caring Theory on mothers' perceptions of breastfeeding self-efficacy and type of breastfeeding. METHODS: The randomized controlled prospective study was conducted with 100 Turkish women (intervention: 50; control: 50) between 2019 and 2021 at a university hospital in Izmir. The intervention program included Human Caring Theory-based face-to-face sessions, for 12 hours, asynchronous distance education modules, and telephone support process. Individual asynchronous distance education and telephone support based on Human Caring Theory were provided from the prenatal process to the sixth month postpartum. The control group received two hours of standard breastfeeding training in a childbirth education class. Clinical trial number was received (NCT05246748). RESULTS: Human Caring Theory-based breastfeeding education and support program improved breastfeeding self-efficacy scores of the intervention group (68.88 ± 3.15) compared to the control group (58.08± 9,92). In addition, the breastfeeding duration and exclusively breastfeeding in the intervention group were longer and statistically higher than the control group. CONCLUSION: Since breastfeeding is an emotional and social interactive process, using the theoretical/philosophical framework based on human care will provide a scientific and holistic perspective. It may be crucial to prefer Human Caring Theory based on routine programs for well-being of breastfeeding rates and successful breastfeeding.